The history and growth of judicial review - Calabresi, Steven G.; Owens, Jasmine M.; Silverman, Bradley G. (Oxford University Press, 2021)
This book examines the origins and growth of judicial review in the key G-20 constitutional democracies, which include: the United States; the United Kingdom; France; Germany; Japan; Italy; India; Canada; Australia; South Korea; Brazil; South Africa; Indonesia; Mexico; and the European Union. The book considers five different theories, which help to explain the origins of judicial review, and it identifies which theories apply best in the various countries discussed. It considers not on what gives rise to judicial review originally, but also what causes of judicial review lead it to become more powerful and prominent over times. The positive account of what causes the origins and growth of judicial review in so many very different countries over such a long period of time has normative implications"--